Analisis Pengukuran Kesehatan Perbankan Syariah Di Indonesia Periode 2020-2022 - Rosyid Rosyid; S.Asriah Immawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this study is to determine the health status of Islamic banking in Indonesia for the period 2020-2022 using the RGEC method (Risk profile, Good Corporate Governance, Income, Capital). Risk profile is represented by NPF and FDR approaches. GCG through 10 management elements. Income is delivered through ROA and ROE. Capital is provided by CAR. Samples were taken from ten Islamic banks that submit financial reports, GCG reports and risk management reports to Bank Indonesia every year. Information of the researched Islamic banks on the official websites of BI, OJK and the websites of each Islamic bank were used for data collection. Quantitative descriptive method was used for data analysis. The results showed that the average condition of Islamic banking from 2020 to 2022 showed an overall rating of 2 or healthy, but had not yet reached level 3 overall. An important study for Islamic banking management is that Islamic banks must continue to increase capital. Then manage risks and implement good management to maintain the bank's operational capacity and be able to compete with conventional banks.